PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PEMBENTUKAN AKHLAK PESERTA DIDIK KELAS X PADA MATA PELAJARAN AKIDAH AKHLAK DI MAN 1 KOTA MAKASSAR - Pratama Kurnia Syarif, Gilang; Syahid, Akhmad; Yunus Anwar, Muh; Mustamin, Mustamin; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the need for Akidah Akhlak learning that does not only emphasize conceptual mastery but also encourages the formation of students Islamic Moral Character in daily life. Problem-Based Learning is considered one of the relevant learning models because it links learning materials with real life problems so that Islamic values can be understood and internalized more meaningfully. This study aims to determine the effect of Problem Based Learning on the formation of students Islamic Moral Character in the Akidah Akhlak subject at MAN 1 Makassar City. This research employed a quantitative approach with a correlational design. The study involved tenth-grade students of MAN 1 Makassar City. The sample was selected using a cluster sampling technique with a total of 79 students. Data were collected through questionnaires and documentation. The research instruments were tested for validity and reliability prior to use. The data analysis techniques used were correlation and multiple linear regression with the assistance of SPSS version 31 for Windows. Based on the results of hypothesis testing, a significance value of < 0.05 was obtained, indicating that there is an effect of Problem Based Learning on the formation of students Islamic Moral Character. Therefore, it can be concluded that Problem Based Learning influences the formation of students Islamic Moral Character in the Akidah Akhlak subject at MAN 1 Makassar City.